Using bodyweight as resistance can be a promising avenue to promote interval training: enjoyment comparisons to treadmill-based protocols - Schaun, G. Z.; Alberton, C. L. (Research Quarterly for Exercise and Sport, 2022)
Purpose: Even though multiple training methods appear to be effective to improve cardiorespiratory fitness, they also need to be perceived as tolerable or enjoyable by exercisers to maximize long-term behavioral maintenance. Therefore, the purpose of the current study was to compare perceived enjoyment between whole-body interval training (SIT-WB), treadmill-based interval training (SIT-T) and moderate-intensity continuous training (MICT).